2014
DOI: 10.1371/journal.pone.0105211
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease among Adult Diabetic Patients Attending a Large Outpatient Diabetic Clinic at a National Referral Hospital in Uganda: A Descriptive Cross Sectional Study

Abstract: BackgroundPeripheral arterial disease (PAD) is one of the recognised diabetic macro vascular complications. It is a marker of generalised systemic atherosclerosis and is closely associated with symptomatic coronary and cerebrovascular disease, hence significant morbidity and mortality. Among African adult diabetic populations, screening and diagnosis of PAD is frequently suboptimal. The aim of this study was to determine the prevalence and associated clinical factors of PAD in adult ambulatory diabetic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
2
21
1
3
Order By: Relevance
“…Eighty seven (59.6%) participants were ≥50 years. 12 An Indian study done by Premalatha, G et al reported mean age of the study group was 59.5±10.1 years and the mean duration of diabetes was 11.7±8.1 years which was similar to present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Eighty seven (59.6%) participants were ≥50 years. 12 An Indian study done by Premalatha, G et al reported mean age of the study group was 59.5±10.1 years and the mean duration of diabetes was 11.7±8.1 years which was similar to present study.…”
Section: Discussionsupporting
confidence: 90%
“…12 Majority of the study participants had symptomatic PAD (59.6%) and mild obstruction (99.3%) according to the ABI measurement. Asymptomatic PAD was noted in 41.4% of the study participants.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, there was no significant difference in the prevalence of PAD among men and women. Other studies also did not identify such association (1,4,13) . According to the PAD pathophysiology, men aged over 45 years and women after menopause are more susceptible to the development of that disease (2)(3) .…”
Section: Métodosmentioning
confidence: 92%
“…O sintoma mais prevalente na DAP é a claudicação intermitente, que consiste na dor em queimação ou em câimbra desencadeada pela marcha, acentuada pela continuação do esforço e que cessa com o repouso (1)(2) . A nível mundial, 202 milhões de pessoas viviam com a doença arterial periférica em 2010, 69,7% deles em paises de baixa renda ou de renda média, incluindo 54,8 milhões no sudeste da Ásia e 45,9 milhões na região do Pacífico ocidental (3) .…”
Section: Introductionunclassified
“…[16,17] In addition, 39% of diabetic patients present with peripheral arterial occlusive disease, [18] and 46% of these patients will sustain a limb amputation. [19] Of the few studies on the benefits of NPWT in the diabetic foot over the last ten years, [1,20] the focus on the use of NPWT to achieve limb salvage in patients with DFU and peripheral arterial disease (PAD) is even rarer.…”
Section: Introductionmentioning
confidence: 99%